Mass production of Carbon Nanotubes from waste cooking palm oil via modified thermal chemical vapor deposition and its application - Norhafizah Jusoh (Tanjong Malim, 2021)
Mass production of Carbon Nanotubes from waste cooking palm oil via modified thermal chemical vapor deposition and its application by Norhafizah Jusoh